The Impacts of COVID-19 on Criminal Legal Proceedings and Victim Advocacy for Sexual Assault Survivors. Issue 2 (17th February 2023) - Javorka, McKenzie; Engleton, Jasmine; Goodman-Williams, Rachael; Gregory, Katie; Campbell, Rebecca
ABSTRACT: This study examines how sexual assault criminal legal proceedings and victim advocacy services for survivors have been impacted by the COVID-19 pandemic. We interviewed 12 victim advocates at a sexual assault service organization in a large Midwestern city that was particularly impacted by the pandemic. Results indicate that there have been major disruptions to sexual assault case timelines and communication with victims. Victim advocacy for survivors has also been affected, especially the provision of court advocacy and accompaniment. We discuss implications of these findings for sexual assault survivors, service providers, and future emergency preparedness planning for the criminal legal system.